IDENTIFY THE RISK TO HOSPITAL ADMISSION IN UK-SYSTEMATIC REVIEW OF LITERATURE - Aramide, Gbolahan; Shona, Kelly; Keith, Burley; Teresa, Bunderson (LIFE: International Journal of Health and Life-Sciences, 2016)
Background: Hospital admissions are the leading cause of increasing healthcare budget and high demand of hospital utilisation in United Kingdom. There is limited information on the predisposing factors into hospital admission. This study systematically summarizes existing result from different studies in order to identify possible risk factors to hospital admission among patients in United Kingdom.Method/ Design: A systematic review of literature was carried out; identified relevant studies from searching through electronic database: Scopus, PubMed, Ethos, Cinahl, Cochrane, Reference list and other relevant reports.Discussion/ Outcome: Our inclusion criteria identified nine studies; using a predefined inclusion criterion, with factors such as: population setting, study design, risk factors, methodology, drawbacks and a systematically reviewed outcome. This study identified significant risk factors such as: older age, comorbidities, sex and deprivation. The review showed that identified risk factors are highly associated with hospital admission; thus early intervention on identified risk factors could reduce the rate of hospital admission in United Kingdom.